REDUPLICATION SYSTEM OF HATAM: FORM AND FUNCTION - Alfons N. Arsai (Program Magister Linguistik Universitas Udayana, 2010)
Hatam is one of the vernaculars spoken in Papua which is categorized into West Papuan phylum and Eastern bird Head sub phylum of Papuan islands. This article aims to discuss the reduplication system of Hatam in relation to how the reduplicated words are formed, and also to describe Hatam reduplication types, function and the meaning of reduplicated words denote in Hatam. Descriptive qualitative method was employed to analyze the collected data. The research finding shows that the reduplication systems of Hatam are formed through free morphemes. There are two types of Hatam reduplication:Full and Partial reduplications. Morphologically, Hatam full reduplication derives concrete nouns from nouns and partial reduplication functions to derive nouns from adjectives and nouns from verbs. Syntantically, the Hatam reduplication system appears as Subject, Verb, Object, Adjective/Complement and Adverb. Semantically, the Hatam reduplication reveals plural form, intensification, collectiveness, no action and resemblance.